ANALISIS KESALAHAN PENULISAN PARAGRAF DALAM SKRIPSI MAHASISWA IAIN BUKITTINGGI - Jasmienti Jasmienti (Ta'dib, 2018)
The problem of the research was various unrevealed errors found in students’ theses at  Informatics and Computer Engineering Education  Department of IAIN Bukittinggi. This study is aiming at describing  the errors found in the students’ theses. This is a qualitative research which describes the errors of students’ writing theses. The data were collected through the technique bof documentary study. The source of data was the students’ theses. The research consisted of five phases; Reading, Identifying, Coding, Summarizing, Displaying, and Summarizing the data. The result describes five errors in students’ theses namely: uncohesive, uncoherent, incomplete, undeveloped, and   unsequential arrangement of paragraphs.